Hot shot - Michaels, Fern (Michaels, Fern. Men of the Sisterhood., 2019)
When lawyer Lizzie Fox's husband, Cosmo Cricket, is left critically injured after being shot by an unknown assailant, the men of BOLO Consultants head straight for Las Vegas to comfort Lizzie--and to uncover a dangerous enemy in the City of Sin.